Evolution of dark-matter haloes in a variety of dark-energy cosmologies - Bartelmann, Matthias; Meneghetti, Massimo (Arxiv, 2004)
High-resolution, numerical simulations of 17 cluster-sized dark-matter haloes in eight different cosmologies with and without dynamical dark energy confirm the picture that core halo densities are imprinted early during their formation by the mean cosmological density. Quite independent of cosmology, halo concentrations have a log-normal distribution with a scatter of ~0.2 about the mean. We propose a simple scaling relation for halo concentrations in dark-energy cosmologies.
Gesehen am 26.09.2017